REASON AND REVOLUTION - Marcuse, Herbert, 1898-1979. ([S.l.])
1 online resource
Keywords: Few philosophers have had a more lasting impact on the philosophy of history than Friedrich Hegel. Reason and Revolution is Herbert Marcuse's brilliant interpretation of Hegel's philosophy and the influence it has had on political thought, from the French Revolution to the twentieth century. In a masterpiece of dialectical thought, Marcuse superbly illuminates the implications of Hegel's philosophy, rescuing it from the taint of reactionary thought that distorted or dismissed it for the early part of the twentieth century. After a masterful survey of the main elements of Hegel's philosophical system, Marcuse argues that it is Hegel the rationalist and progressive who stands in contrast to the irrationalism of Nazism, providing the crucial platform on which Marxist thought would later build and take Hegel's thought in a radical and explosive new direction. A vital book in the development of critical theory and for understanding the great battle between liberal and reactionary thought, Reason and Revolution remains essential reading today. This Routledge Classics edition includes a new Foreword by J.M. Bernstein.